HyFlex EDM: superficial features, metallurgical analysis and fatigue resistance of innovative electro discharge machined NiTi rotary instruments. (19th June 2015) - Pirani, C.; Iacono, F.; Generali, L.; Sassatelli, P.; Nucci, C.; Lusvarghi, L.; Gandolfi, M. G.; Prati, C.
Abstract: Aim: To evaluate the surface and microstructural alterations of new and used HyFlex EDM prototypes and to test their fatigue resistance. Methodology: Fifteen HyFlex EDM prototypes were used for in vitro instrumentation of severely curved root canals. Surface and microstructural characteristics of new and used files were compared by ESEM analysis equipped with energy dispersive X‐ray spectrophotometry (EDS) and optical metallographic imaging. Usage‐induced degradation was assessed. Thirty additional HyFlex EDM prototypes and 20 standard manufactured HyFlex CM files were subjected to cyclic fatigue tests. Time to fracture was recorded, and results were validated using the Kruskal–Wallis test (α‐level 0.05). Fatigued files were analysed by ESEM for fractographic evaluation. Results: Surface and microstructural characterization of EDM prototypes revealed the typical spark‐machined surface of a NiTi EDM alloy. No fractures were registered during root canal instrumentation. No evident surface alterations and minor degradation were observed between new and used instruments. The metallographic analysis of new and used files disclosed a homogeneous structure, mostly composed of lenticular martensite grains, and some residual austenite. The cyclic fatigue test showed an increase of fatigue resistance up to 700% on the EDM compared to CM files. Conclusions: Spark‐machined peculiar surface is the main feature of HyFlex EDM. Low degradation was observed after multiple canal instrumentations. Prototypes exhibited surprising high values of cyclic fatigue resistance and a safe in vitro use in severely curved canals.